DISCOVERY LEARNING MODEL BASED ON LITERACY COLLABORATION IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT MAN 2 PONOROGO - Devid Dwi Erwahyudin (Jurnal Scientia, 2023)
Students who are not actively involved when learning takes place in the classroom result in inhibition of thinking skills and confusion in facing the process to get the final result. This is because the use of strategies or learning models applied is not appropriate, so it does not encourage an active learning atmosphere in the classroom. Today's school learning models are constantly evolving and changing to help students learn actively and effectively. Students must be able to connect learning materials with real events that occur in everyday life in their environment. The research conducted at MAN 2 Ponorogo aims to find out how teachers apply the Discovery learning model based on literacy collaboration in Islamic religious education subjects. Researchers use qualitative descriptive methods and get the result that students can understand the subjects as they experience the process of finding themselves. On the other hand, the disadvantage of this learning model is that it must take a lot of time if it is not guided and directed properly